2018
DOI: 10.1093/jrr/rry059
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical features of prostate-specific antigen bounce after 125I brachytherapy for prostate cancer

Abstract: The aim of this study was to analyse the clinical features of prostate-specific antigen (PSA) bounce and the difference between biochemical failure and large-magnitude PSA bounce. The cases of 352 patients with prostate cancer who underwent brachytherapy were analysed. PSA bounce was defined as an increase in PSA of ≥0.2 ng/ml above an initial PSA nadir, with subsequent decline to or below that initial nadir without treatment. PSA bounce +2 was defined as an increase in PSA of ≥2.0 ng/ml above the nadir with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A systematic literature review was performed to identify studies reporting PSA bounce post-radiotherapy (see Materials and Methods for details) ( Figure 1 ). The search identified 50 studies including 26,258 patients, which were included in the analysis ( Table 1 ) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. The number of studies and patients stratified by modality is summarized in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic literature review was performed to identify studies reporting PSA bounce post-radiotherapy (see Materials and Methods for details) ( Figure 1 ). The search identified 50 studies including 26,258 patients, which were included in the analysis ( Table 1 ) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. The number of studies and patients stratified by modality is summarized in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The number of studies and patients stratified by modality is summarized in Table S1. Among the 50 studies, eight were prospective observational studies [14,15,17,32,[39][40][41]50] and the others were retrospective observational studies. A meta-analysis showed that the rate of PSA bounce for all studies was 31% (95% confidence interval (CI), 28-33%) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Prostate-specific antigen (PSA) "bounce," a transient rise in PSA post-therapy, can happen after either brachytherapy (BT) or external beam radiation therapy (EBRT); however, it is more common in the former case (1,2). In general, PSA bounce tends to occur within 2-3 years of treatment, rarely exceeds levels of 2-3ng/ml above the nadir PSA and tends to resolve over 6-12 months (2).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate-specific antigen (PSA) "bounce," a transient rise in PSA post-therapy, can happen after either brachytherapy (BT) or external beam radiation therapy (EBRT); however, it is more common in the former case (1,2). In general, PSA bounce tends to occur within 2-3 years of treatment, rarely exceeds levels of 2-3ng/ml above the nadir PSA and tends to resolve over 6-12 months (2). Studies have shown that PSMA PET/CT (Prostate-specific membrane antigen positron emission tomography/Computational Tomography) has a high sensitivity and specificity for the detection of prostate cancer recurrence and can potentially guide therapy (3).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with high-risk disease received ADT and BT followed by EBRT. Our implant procedure was previously described in detail [ 9 ]. We implanted the 125 I sources using a modified peripheral loading pattern for seed placement.…”
Section: Introductionmentioning
confidence: 99%